Innovative Approaches Supporting Social Change, Improved Quality of Human Life, and Enhanced Planetary Consciousness Across Europe - Dryjanska, Laura; Krzyworzeka, Pawel (Studia Ecologiae et Bioethicae, 2024)
This research uses a dialogical approach to the theory of social representations to investigate examples of social innovation in volunteer and community projects across Europe. Social representational processes shape public agendas and determine which issues are put forward. One example of this dynamic communicative exchange is the annual Social Innovation Competition of the European Innovation Council, for which an award is given each year. The study looks at a total of 36 projects that won awards over 10 years of the competition in Europe. Our archival research focuses on and discusses the co-construction of the meaning of innovation in relation to ecology. The analysis concentrates on the countries of origin of the projects, as well as the thematic areas, in relation to the themes of social innovation selected by the European Innovation Council. In this process, three crucial voices are examined, including the voice of the European Innovation Council, voice of the innovator in each award-winning project, and voice of the general public. The results indicate that members of volunteer and community sectors propose socially innovative initiatives, especially in the areas of enhancing planetary consciousness and improving the quality of human life.